(untitled) (Bangladesh Journal of Medical Microbiology, 2017)
Urinary tract infection (UTI) is the most common infectious complications after renal transplantation. Recently many researchers reported that the bacterial agents of UTI in renal allograft recipients changed and demonstrated increased antimicrobial resistance to commonly used cephalosporins. This study was undertaken to isolate the bacteria which are responsible for UTI and their susceptibility pattern for appropriate antibiotic therapy in renal allograft recipients. This was an observational study conducted in the Department of Microbiology Bangabandhu Sheikh Mujib Medical University (BSMMU) from December 2010 to 2011. Twenty one renal allograft recipients from Department of Nephrology were evaluated for UTI after surgery up to six weeks. Microscopic examination, culture and sensitivity of urine specimen were performed. Out of 21 renal allograft recipients, 13 (61.90%) patients developed UTI during initial post transplant period. Of 69 urine specimens collected from them 22(31.88%) yielded positive results for culture. Enterococcus spp. (50%) was the major bacterial pathogen isolated and showed 100% resistance to Cefuroxime, Ceftriaxone and Ceftazidime. Enterococcus spp. is an emerging pathogen responsible for development of UTI in renal allograft recipients which showed 100% resistance to 2nd and 3rd genaration cephalosporin group. Bangladesh J Med Microbiol 2015; 9 (1): 13-16